2018
DOI: 10.1038/nchembio.2558
|View full text |Cite
|
Sign up to set email alerts
|

Lytic xylan oxidases from wood-decay fungi unlock biomass degradation

Abstract: Wood biomass is the most abundant feedstock envisioned for the development of modern biorefineries. However, the cost-effective conversion of this form of biomass into commodity products is limited by its resistance to enzymatic degradation. Here we describe a new family of fungal lytic polysaccharide monooxygenases (LPMOs) prevalent among white-rot and brown-rot basidiomycetes that is active on xylans-a recalcitrant polysaccharide abundant in wood biomass. Two AA14 LPMO members from the white-rot fungus Pycno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
266
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(290 citation statements)
references
References 52 publications
6
266
4
4
Order By: Relevance
“…This new family, named AA14, is distantly related to other LPMO families with the main activity to cleave xylan with oxidation of C-1, which has been demonstrated for two AA14 LPMOs from fungus Pycnoporus coccineus [75]. They are currently categorized as families 9, 10, 11, 13 14, and 15 of the auxiliary activities.…”
Section: Lytic Polysaccharide Monooxygenase Enzymesmentioning
confidence: 87%
See 1 more Smart Citation
“…This new family, named AA14, is distantly related to other LPMO families with the main activity to cleave xylan with oxidation of C-1, which has been demonstrated for two AA14 LPMOs from fungus Pycnoporus coccineus [75]. They are currently categorized as families 9, 10, 11, 13 14, and 15 of the auxiliary activities.…”
Section: Lytic Polysaccharide Monooxygenase Enzymesmentioning
confidence: 87%
“…They are able to degrade insoluble polysaccharides such as crystalline cellulose, chitin and starch [71][72][73][74]. Also, they depolymerise noncrystalline or soluble hemicellulosic substrates such as xyloglucan, xylan, and beta-glucans [75]. LPMOs are important in biomass conversion because they act in synergy with glycoside hydrolase (GH), thereby enhancing overall polysaccharide conversion efficiency.…”
Section: Lytic Polysaccharide Monooxygenase Enzymesmentioning
confidence: 99%
“…Lytic polysaccharide monooxygenases (LPMOs, EC: 1.14.99.53-56, CAZy IDs: AA9-11, AA13-16) are copper-containing enzymes found in chitin-, starch-, and plant cell wall-degrading organisms [1][2][3][4][5]. LPMOs use an unprecedented oxidative reaction mechanism to cleave and locally decrystallize these biopolymers, which enhances the activity of associated hydrolases [1,2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…AA9 LPMOs have been shown to possess different substrate preferences in terms of activities against cellulosic and hemicellulosic substrates, indicating that LPMOs could be recruited for degradation of different polysaccharide components in plant cell walls [18,26,3237]. They have also been shown to boost the hydrolytic activity of cellulases in terms of saccharification of lignocellulosic substrates [27,3844], and several AA9 LPMOs show effects of separating fibrils from cellulose fibrillar structures, pointing at important roles in cellulose decrystallization [4547]. Furthermore, studies with atom force microscopy have revealed that modification of highly resistant microfibril bundles by oxidative cleavage using a C1-oxidizing LPMO could enhance the digestion of crystalline regions by a processive cellobiohydrolase I, providing insights into synergistic cooperation between LPMO and cellulase enzymes [45].…”
Section: Introductionmentioning
confidence: 99%
“…irregulare has been sequenced and annotated, and was found to encode ten putative AA9 LPMOs [16]. More recently, two putative AA14 LPMOs were also discovered in its genome (GenBank ID: XP_009545121.1 and XP_009545122.1) [27]. All of the ten H .…”
Section: Introductionmentioning
confidence: 99%